Unveiling the link between occupational heat strain and productivity loss: evidence from South Indian informal sectors - Vidhya Venugopal; Tanya Isaac; K. G. Gayathri; Sajeeth Kumar; P. K. Latha; Rekha Shanmugam (Discover Public Health)
Abstract Introduction In an economy like India where the informal sector dominates, occupational heat stress poses significant challenges to worker productivity. This cross-sectional study investigates the impact of heat exposure on worker productivity across occupational groups. Methods We used mixed-effect logistic regression models to investigate the relationship between predictive factors of heat stress and lost productivity. We monitored heat exposures with the Wet Bulb Globe Temperature monitor and established methods to collect quantitative data on physiological heat strain and self-reported productivity loss through validated questionnaires. Results Dehydration emerged as a significant predictor of productivity loss [OR = 11.62 (95% CI 8.68, 14.56); p = 0.05], underscoring its critical role in productivity drop. Workload had a strong influence, with a 2% increase in the likelihood of productivity loss for each 120-W increase in workload [OR = 1.02 (95% CI 0.63, 1.41); p = 0.02]. Older workers and females are particularly susceptible to productivity loss, as each degree increase in WBGT increases the likelihood of such losses by 44% for older workers and 339% for female workers. The odds ratio for WBGT-industry interactions is 16.73, with informal sector workers experiencing the greatest productivity loss as a result of heat stress. The strong inverse correlation between productivity loss and acclimatization suggests that physiological adaptation to heat provides substantial protection. Conclusion This study highlights how environmental, physiological, and demographic factors affect heat-induced productivity loss. Results show that targeted interventions, especially in the informal sector, are needed to protect worker productivity and reduce heat stress.